2020
DOI: 10.1016/j.pedn.2020.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Nurses' Turnover Intention and Its Association with Calling in China's Tertiary Hospitals

Abstract: To examine the turnover intention of Chinese pediatric nurses, its influential socio-demographic factors, and the association with calling and job satisfaction. Design and methods: We randomly surveyed 10% of the nurses from 50% of the children's tertiary hospitals nationwide in China. Data were collected on nurses' turnover intention and associated factors such as age, income, skill level, working years, job satisfaction, and calling in 2017. Results: In total, 547 nurses were surveyed, and the response rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 26 publications
6
25
0
10
Order By: Relevance
“…36 Shanshan Xu's research proved the high turnover rate of Chinese pediatric nurses. 37 The second was that the respondents of the pediatric satisfaction questionnaire were usually the guardian of the patients, both of them would directly affect the accuracy of result. For Chinese hospitals, in most cases, outpatient surgery would be affected by limited medical resources, environmental noise caused by patients' symptoms, and hygiene problems caused by excessive staff.…”
Section: Dovepressmentioning
confidence: 99%
“…36 Shanshan Xu's research proved the high turnover rate of Chinese pediatric nurses. 37 The second was that the respondents of the pediatric satisfaction questionnaire were usually the guardian of the patients, both of them would directly affect the accuracy of result. For Chinese hospitals, in most cases, outpatient surgery would be affected by limited medical resources, environmental noise caused by patients' symptoms, and hygiene problems caused by excessive staff.…”
Section: Dovepressmentioning
confidence: 99%
“…Turnover in nursing staff is a major contributor to nurse shortages, which in turn can lead to increased stress among nurses (Kaddourah, Abu‐Shaheen, & Al‐Tannir, 2018). Several factors may contribute to turnover of nursing staff, including job stress, little attention from administrators, dissatisfaction with work environment, long working shifts, low income and negative relationships with colleagues (Asegid, Belachew, & Yimam, 2014; Mudallal, Othman, & Al Hassan, 2017; Xu, Tao, Huang, Little, & Huang, 2020; Yang, Lv, Zhou, Liu, & Mi, 2017a). Previous evidence showed that turnover intention was strongly intercorrelated with job burnout (Scanlan & Still, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Good interpersonal relationship with colleagues may help to form a closer emotional connection [53]. When employees are in a bad mood and need care, they are more likely to be comforted by colleagues if they have good interpersonal relationship, which can reduce depression and conflicts in workplace [54]. Such a good state of interpersonal relationship may have an impact on the effectiveness and efficiency of communication, social exchanges, and emotional venting among employees and contributes to carry out more harmonious cooperation and form a good working atmosphere [55].…”
Section: Interpersonal Relationshipmentioning
confidence: 99%